FORMULASI SEDIAAN SALEP DAN UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN BIDARA ARAB (Ziziphus spina-christi (L.) Desf) TERHADAP BAKTERI Staphylococcus Epidermidis - alviony trista hapsari; Galih Samodra (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2022)
Ointment is a semi-solid preparation that is used topically. Arabic bidara leaves contain secondary metabolites in the form of saponins, tannins, alkaloids, polyphenols and flavonoids which can inhibit the antibacterial growth of Staphylococcus epidermidis so that it can be made in ointment preparations. The purpose of thi study was to determine the physical properties and zone of inhibition of the formulation of the ethanol extract of bidara arabic leaf ointment. Extraction using remaceration method with 70% ethanol solvent was formulated using a water-soluble ointment base in the from of PEG 400 and PEG 4000. Made in 3 variations of extract concentration 40%, 50%, 60%. Furthermore, the evaluation of the preparation include: organoleptic test, homogeneity, pH, disperbility, adhesion. The results of the One Way ANOVA analysis showed that there werw differences in the pH test, dispersion and adhesion with a p-value of <0,05 the homogeneity test showed differences during storage for 6 cycles, while the organoleptic test was in a stable state during storage. The results obtained showed that the preparation of bidara arabic leaf extract ointment was able to inhibit the growth of Staphylococcus Epidermidis bacteria, namely the FI of 9.16±0.76 mm, FII of 8.56±1.01 mm and FIII of 10.08±0.10 mm is included in the medium category.